Are early onset aging conditions correlated to daily activity functions in youth and adults with Down syndrome?. (January 2015) - Lin, Jin-Ding; Lin, Lan-Ping; Hsu, Shang-Wei; Chen, Wen-Xiu; Lin, Fu-Gong; Wu, Jia-Ling; Chu, Cordia
Highlights: To investigate the relation of early onset aging and ADL in persons with DS. Onset aging conditions can significantly predicted the variation in ADL scores. We should initiate early intervention programs to improve their healthy aging and ADL functions. Abstract: This study aims to answer the research question of "Are early onset aging conditions correlated to daily activity functions in youth and adults with Down syndrome (DS)?" A cross-sectional survey was employed to recruit 216 individuals with DS over 15 years of age in the analyses. A structured questionnaire included demographic data, brief self-reported aging conditions, Dementia Screening Questionnaire for Individuals with Intellectual Disabilities (DSQIID) and activity of daily living (ADL) scales were completed by the primary caregivers who were well-suited for providing information on the functioning conditions of the DS individuals. Results showed that the most five frequent aging conditions (sometimes, usually and always) included frailty (20.2%), vision problem (15.8%), loss of language ability (15.3%), sleep problem (14.9%) and memory impairment (14.5%). Other onset aging conditions included more chronic diseases (13.9%), hearing loss (13%), chewing ability and tooth loss (12.5%), incontinence (11.1%), depressive syndrome (7.7%), falls and gait disorder (7.2%), loss of taste and smell (7.2%). The data also showed scores of DSQIID, onset aging conditions and ADL has significant relationships each other in Pearson's correlation tests. Finally, multiple linear regression analyses indicated onset aging conditions ( β = −0.735, p < 0.001) can significantly predicted the variation in ADL scores after adjusting other factors ( R 2 = 0.381). This study suggests that the authority should initiate early intervention programs aim to improve healthy aging and ADL functions for people with DS.